Sustainability-Linked Bonds Research: A Bibliometric and Content Analysis Review - Clarisse Heck Machado; Miguel Sousa; Manuel Castelo Branco (International Journal of Financial Studies, 2025)
One of the most significant recent developments in the debt financing sector pertains to new products and standards applicable to sustainability-related issues. Therefore, research on this has increased substantially. One of the most recent such developments is that of sustainability-linked bonds (SLBs). In 2023, global sustainable bond issuance experienced an increase of three percent, nearly reaching USD 1 trillion with significant shifts observed in categories, including green-, social-, sustainability-, and sustainability-linked bonds (GSSSBs). This paper presents one of the most extensive literature reviews on SLBs research, examining trends, research evolution, thematic landscape, and underexplored topics by employing bibliometric and content analysis approaches. It identifies future research avenues and trends, including supporting issuers in transitioning towards net-zero emissions or broader objectives, such as implementing sustainability targets to fight climate change, the premium associated with bond pricing, the potential for greenwashing, and the blockchain technology for issuance and target’s monitoring transparency. In addition, this paper discusses the new trend of thematic bonds, such as those addressing gender characteristics, as innovative strategies to promote societal equity. The systematic literature review also explores the significance of SLBs as public instruments, like sovereign bonds or private instruments, while identifying research areas, including linking SLBs with the evolution of management theory.